CHEMICAL COMPOSITION AND FEED VALUE OF WORMWOOD (Artemisia Diffusa H. Krasch): https://doi.org/10.5281/zenodo.14233216 - Yakhyaev , B; Klichev , Z; Jemler , Buijs (International scientific and practical conference, 2024)
Pasture livestock farming is one of the main branches of agriculture in Uzbekistan. This industry is characterized by high profitability of production due to the efficient use of natural pasture resources with low costs of production